2020
DOI: 10.3390/ani11010057
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Medium-Chain α-Monoglycerides on the Growth Performance, Intestinal Histomorphology, Amino Acid Digestibility, and Broiler Chickens’ Blood Biochemical Parameters

Abstract: This trial was conducted to assess the impact of medium-chain α-monoglycerides, glycerol monolaurate (GML) supplementation on the growth performance, apparent ileal digestibility coefficient (AID%) of amino acids, intestinal histomorphology, and blood biochemical parameters of broiler chickens. Three-day-old chicks (76.82 g ± 0.40, n = 200) were haphazardly allocated to four experimental groups with five replicates for each (10 chicks/replicate). The treatments consisted of basal diets supplemented with four g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 69 publications
4
43
0
Order By: Relevance
“…The overall performance showed a linear increase in the BW, BWG, PER, and RGR and a linear decrease in the FCR at 0.75% dietary level of GLM and oregano EO compared to the control and the optimum dietary level of GLM and oregano EO blend detected using broken-line regression model was 0.58% based on the data of final BW and FCR. The improved growth can be attributed to the improvement of most intestinal morphometrics, which leads to an increase in the absorption surface available for the absorption of nutrients essential for growth [ 9 , 19 ]. However, dietary GLM and oregano EO blend had an insignificant impact on the AID% of most identified essential AA, with significant declines in AID% of threonine and arginine at different dietary levels of supplemented additives.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The overall performance showed a linear increase in the BW, BWG, PER, and RGR and a linear decrease in the FCR at 0.75% dietary level of GLM and oregano EO compared to the control and the optimum dietary level of GLM and oregano EO blend detected using broken-line regression model was 0.58% based on the data of final BW and FCR. The improved growth can be attributed to the improvement of most intestinal morphometrics, which leads to an increase in the absorption surface available for the absorption of nutrients essential for growth [ 9 , 19 ]. However, dietary GLM and oregano EO blend had an insignificant impact on the AID% of most identified essential AA, with significant declines in AID% of threonine and arginine at different dietary levels of supplemented additives.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, arginine is identified for its role as a precursor for the production of polyamines, nitric oxide, and creatine and its ability to promote insulin growth factor release, which has a variety of biological roles [ 24 ]. We previously demonstrated that broilers fed graded levels of GLM had no improvement in growth performance traits [ 9 ], suggesting that combined supplementation of GLM with oregano EO could increase chicken growth performance moderately. This improvement may be due to the presence of EO, which provides active components of antimicrobial, antifungal, and antioxidant properties, which all positively impact growth performance in terms of FCR and PER [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The average initial body weight (BW) was recorded at the beginning of the experiment. The BW was then determined every week, and body weight gain (BWG) was determined [ 19 ]. The difference between the weight of the provided feed and the feed that remained was used to calculate feed intake (FI) per replicate.…”
Section: Methodsmentioning
confidence: 99%
“…Under standard esterification conditions, monoglycerides tend to prefer the 1-monoglyceride form rather than the 2-monoglyceride form. Medium-chain monoglyceride have shown promising effects on feed efficiency, health improvement, growth performance capacity and immune status of broilers ( Fortuoso et al., 2019 ; Valentini et al., 2020 ; Amer et al., 2021 ). Monoglycerides are natural compounds which, alongside their nutritional values of lipids, act against gram-positive and gram-negative bacteria at concentrations at which no evidence for harm to the body has been found ( Mansour and Millière, 2001 ; Thormar et al., 2006 ).…”
Section: Introductionmentioning
confidence: 99%